1997
DOI: 10.1093/oxfordjournals.molbev.a025818
|View full text |Cite
|
Sign up to set email alerts
|

Nonneutral evolution of tandem repeats in the mitochondrial DNA control region of lagomorphs

Abstract: The mitochondrial DNA of the European rabbit (Oryctolagus cuniculus) contains a tandem array of 153-bp repeats in the vicinity of the replication origin of the H-stand. Variation among molecules in the number of these repeats results in inter- and intraindividual length polymorphism (heteroplasmy). Generally, in an individual, one predominant molecular type is observed, the others representing a low percentage of the mtDNA content. At the tissue level, we observe a particular distribution of this polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 27 publications
3
59
0
Order By: Relevance
“…As mtVNTRs are frequently hypervariable, and drift (and/or selection) may rapidly change the frequencies of mtDNA polymorphisms (Koehler et al 1991;Jenuth et al 1997), different tissue types or body locations can contain significantly different frequencies or classes of mtVNTR. The distribution of mtDNA point mutations in mice (Jenuth et al 1997) and of mtVNTRs in rabbits (Casane et al 1994) have revealed that different tissue types contain variable allele frequencies which seem to be brought about by both drift and tissue-specific selection. Such tissue-specific mtDNA compositions also seem to play an important role in several human pathologies (Wallace 1994).…”
Section: Nonhomogeneous Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…As mtVNTRs are frequently hypervariable, and drift (and/or selection) may rapidly change the frequencies of mtDNA polymorphisms (Koehler et al 1991;Jenuth et al 1997), different tissue types or body locations can contain significantly different frequencies or classes of mtVNTR. The distribution of mtDNA point mutations in mice (Jenuth et al 1997) and of mtVNTRs in rabbits (Casane et al 1994) have revealed that different tissue types contain variable allele frequencies which seem to be brought about by both drift and tissue-specific selection. Such tissue-specific mtDNA compositions also seem to play an important role in several human pathologies (Wallace 1994).…”
Section: Nonhomogeneous Tissuesmentioning
confidence: 99%
“…Wilkinson & Chapman (1991) studied mtVNTR copy-number changes in motherÐoffspring pairs of the evening bat Nycticeius humeralis and estimated a per generation mutation rate of 10 Ð2 . MotherÐoffspring pairs of European rabbits have been used to estimate a very similar (10 Ð2 ) per generation mutation rate (Casane et al 1994). Typical values for accumulation of mtDNA point mutations in humans have been thought to be in the order of 10 Ð6 Ð10 Ð8 (estimated from Brown et al 1979; Kondo et al 1993).…”
Section: Mutation Rates In Mtvntrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabbit articular chondrocytes were used for two reasons: morphologic changes of in vitro senescent cells are close to changes observed in degenerative articular pathologies found in old people [19]; rabbit mtDNA contains repeated sequences whose generation and maintenance suppose additions, deletions and rearrangements of units [20], furthermore a slight bias in their frequencies was observed in some tissues of old animals [21].…”
Section: Introductionmentioning
confidence: 99%